Brain-Derived Neurotrophic Factor Inhibits the Function of Cation-Chloride Cotransporter in a Mouse Model of Viral Infection-Induced Epilepsy - Patel, Dipan C.; Thompson, Emily G.; Sontheimer, Harald (Frontiers in Cell and Developmental Biology, 2022)
Well over 100 different viruses can infect the brain and cause brain inflammation. In the developing world, brain inflammation is a leading cause for epilepsy and often refractory to established anti-seizure drugs. Epilepsy generally results from an imbalance in excitatory glutamatergic and inhibitory GABAergic neurotransmission. GABAergic inhibition is determined by the intracellular Cl- concentration which is established through the opposing action of two cation chloride cotransporters namely NKCC1 and KCC2. Brain-derived neurotrophic factor (BDNF) signaling is known to regulate expression of KCC2. Hence we hypothesized that viral induced epilepsy may result from aberrant BDNF signaling. We tested this hypothesis using a mouse model of Theiler’s murine encephalomyelitis virus (TMEV) infection-induced epilepsy. We found that BDNF levels in the hippocampus from TMEV-infected mice with seizures was increased at the onset of acute seizures and continued to increase during the peak of acute seizure as well as in latent and chronic phases of epilepsy. During the acute phase of epilepsy, we found significant reduction in the expression of KCC2 in hippocampus, whereas the level of NKCC1 was unaltered. Importantly, inhibiting BDNF using scavenging bodies of BDNF in live brain slices from TMEV-infected mice with seizures normalized the level of KCC2 in hippocampus. Our results suggest that BDNF can directly decrease the relative expression of NKCC1 and KCC2 such as to favor accumulation of chloride intracellularly which in turn causes hyperexcitability by reversing GABA-mediated inhibition. Although our attempt to inhibit the BDNF signaling mediated through tyrosine kinase B – phospholipase Cγ1 (TrkB-PLCγ1) using a small peptide did not change the course of seizure development following TMEV infection, alternative strategies for controlling the BDNF signaling could be useful in preventing seizure generation and development of epilepsy in this model.